Does rhythmic auditory stimulation compared to no rhythmic auditory stimulation improve patient's static and dynamic standing balance post stroke?. (3rd September 2019) - Pfeiffer, Kathryn; Clements, Jacob; Smith, McKayla; Gregoire, Matthew; Conti, Christopher
Abstract: Background: Rhythmic auditory stimulation (RAS) uses music or a metronome to stimulate the audio-motor pathway in the brain. This type of stimulation uses external auditory cueing to try to create movement that is rhythmical. This has been shown to improve gait. This systematic review seeks to determine if the same benefits are seen in static and dynamic standing balance. Methods: Four researchers conducted an online search of Cochrane, Pubmed, Europe PMC, and J Stage on December 10 th and December 11 th, 2018. Each researcher assessed all abstracts and were then paired and assigned to each qualifying article. Quality of the selected articles was scored with two tools. Each article was summarized and the results were discussed. We screened 38 abstracts and 5 articles were used to conduct this systematic review. Results: Statistically significant results were shown in at least one objective measure in each of the five selected studies. Rhythmic Auditory Stimulation showed improvement with a P value less than .05 in patients post stroke within the past 2 years. Conclusions: Using RAS showed improvement in balance when compared to a control group in patients after experiencing a stroke. These findings can greatly assist clinicians when searching for the most effective interventions for patients after stroke who are experiencing difficulty with balance and gait. More research is needed to determine the long-term effects of RAS treatment using larger sample sizes and in the acute and subacute time frames of patients post-stroke.